A Fair Share of Tax A Fiscal Anthropology of Contemporary Sweden - Björklund Larsen, Lotta (Springer Nature, 2018)
Tax compliance; Reciprocity; Ethnography; Economic anthropology; Welfare; Exchanges; Taxpayer; Marcel Mauss; Swedish Tax Agency; quid-pro-quo exchange; Fiscal anthropology; Swedish tax; Behavioural economics; Economic exchanges and reciprocity; Tax as a gift; Public economics; Progressive marginal tax; Contributive and distributive balancing